2021
DOI: 10.1002/nafm.10510
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Simulated Effects of Length‐Based Trophy Regulations for Flathead and Channel Catfish in the Lower James River, South Dakota

Abstract: Catfish are popular with anglers fishing southeastern South Dakota rivers, and a group of anglers has expressed concern about the perceived overharvest of trophy‐size catfish. However, existing data are insufficient for determining whether Flathead Catfish Pylodictis olivaris and Channel Catfish Ictalurus punctatus are being overharvested. Our objective was to determine the population dynamics of Flathead and Channel catfish and model potential outcomes of length‐based trophy regulations (one fish and no fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(143 reference statements)
1
6
0
Order By: Relevance
“…Annual exploitation rates in rivers range from 4.5% to 19.0% (Schall and Lucchesi 2021;Winders and McMullen 2021), and those in reservoirs range from 0% to 13% (Marshall et al 2009a;Sullivan and Vining 2011;Travnichek 2011a;Bodine et al 2016). These low annual mortality and exploitation rates are consistent with longlived species (e.g., 34 years as reported by Marshall et al 2009b), and this further suggests that overharvest is possible if angling pressure is high in a given location.…”
Section: Mortality Rates and Exploitationsupporting
confidence: 62%
See 3 more Smart Citations
“…Annual exploitation rates in rivers range from 4.5% to 19.0% (Schall and Lucchesi 2021;Winders and McMullen 2021), and those in reservoirs range from 0% to 13% (Marshall et al 2009a;Sullivan and Vining 2011;Travnichek 2011a;Bodine et al 2016). These low annual mortality and exploitation rates are consistent with longlived species (e.g., 34 years as reported by Marshall et al 2009b), and this further suggests that overharvest is possible if angling pressure is high in a given location.…”
Section: Mortality Rates and Exploitationsupporting
confidence: 62%
“…2006; Makinster and Paukert 2008; Hamel et al. 2021; Schall and Lucchesi 2021), from 0.11 to 0.40 in reservoirs (Winkelman 2011; Stubbs et al. 2015; Lucchesi et al.…”
Section: Mortality Rates and Exploitationmentioning
confidence: 99%
See 2 more Smart Citations
“…For Iowa reservoirs, researchers suggested that a protected slot length limit or a maximum length limit would increase the size structure of Flathead Catfish populations (Muhlbauer and Krogman 2021, this special issue). Conversely, restrictive harvest regulations may not be successful in the development of trophy Flathead Catfish fisheries when slow growth and high natural mortality prevent individuals from reaching trophy sizes (Schall and Lucchesi 2021, this special issue). An increased minimum length limit was suggested to increase abundance of large Blue Catfish without reducing yield in a Missouri population characterized by slow growth (Michaletz et al.…”
Section: Summary Of Progressmentioning
confidence: 99%